^ 3 sqrt 750 + ^ 3 sqrt 2058 - ^ 3 sqrt 48
Rewriting the expression we have
^ 3 sqrt (6 * x ^ 3) + ^ 3 sqrt (6 * y ^ 3) - ^ 3 sqrt (6 * z ^ 3)
That is, we have the following equations:
6 * x ^ 3 = 750
6 * y ^ 3 = 2058
6 * z ^ 3 = 48
Clearing x, y and z we have:
x = 5
y = 7
z = 2
Then, rewriting the expression
x (^ 3 sqrt (6)) + y (^ 3 sqrt (6)) - z (^ 3 sqrt (6))
Substituting the values
5 (^ 3 sqrt (6)) + 7 (^ 3 sqrt (6 *)) - 2 (^ 3 sqrt (6))
10 (^ 3 sqrt (6))
answer
the simple form of the expression is
D) 10 ^ 3 sqrt 6
Answer:
((4 choose 3)·(48 choose 2) + (4 choose 4)·(48 choose 1)) / (52 choose 5) = 19/10829 = 0.0018
Answer:
6
Step-by-step explanation:
Answer:
The answer is 3 7/12 Hope this helps :)
Step-by-step explanation: